Enhancing Exoplanet Ephemerides by Leveraging Professional and Citizen Science Data: A Test Case with WASP-77 A b - Noguer, Federico R. (2024)
We present an updated ephemeris, and physical parameters, for the exoplanet WASP-77 A b. In this effort, we combine 64 ground- and space-based transit observations, 6 space-based eclipse observations, and 32 radial velocity observations to produce this target´s most precise orbital solution to date aiding in the planning of James Webb Space Telescope and Ariel observations and atmospheric studies. We report a new orbital period of 1.360029395 ± 5.7 × 10−8 days, a new mid-transit time of 2459957.337860 ± 4.3 × 10−5 Barycentric Julian Date in the Barycentric Dynamical Timescale (BJDTDB) and a new mid-eclipse time of 2459956.658192 ± 6.7 × 10−5 BJDTDB. Furthermore, the methods presented in this study reduce the uncertainties in the planet´s mass 1.6654 ± 4.5 × 10−3MJup and orbital period 1.360029395 ± 5.7 × 10−8 days by factors of 15.1 and 10.9, respectively. Through a joint fit analysis comparison of transit data taken by space-based and citizen science-led initiatives, our study demonstrates the power of including data collected by citizen scientists compared to a fit of the space-based data alone. Additionally, by including a vast array of citizen science data from ExoClock, Exoplanet Transit Database, and Exoplanet Watch, we can increase our observational baseline and thus acquire better constraints on the forward propagation of our ephemeris than what is achievable with Transiting Exoplanet Survey Satellite data alone.